PERTANGGUNGJAWABAN PT. GRAB TEKNOLOGI INDONESIA TENTANG PENCAIRAN DANA TERHADAP RESTORAN SEBAGAI PENGGUNA JASA GRABFOOD: Liability of PT. Grab Teknologi Indonesia Regarding Fund Disbursement to Restaurants as GrabFood Merchants - Azzahra, Mutiara; Anggraini, Anna Maria Tri (Faculty of Law, Universitas Trisakti, 2024)
Consumers using online food delivery applications that provide electronic payment in 2020 increased to date. One of the most used services by consumers in Indonesia is GrabFood, created by PT. Grab Technology Indonesia. In practice, the system for fund claim service provided does not follow the Restaurant's agreement as a Merchant. This study analyse how PT. Grab Teknologi Indonesia violates the UUPK. This study also analysed the fund claim method based on Law No. 8 of 1999 Consumer Protection (UUPK) between PT. Grab Teknologi Indonesia as a GrabFood service provider and Restaurant Menepi Kitchen as a merchant. This study uses normative and descriptive research methods based on secondary and primary data as supporting data and to obtain conclusions deductively. PT. Grab Teknologi Indonesia had violated UUPK article 7, letters a and g regarding the obligation of service providers to provide compensation if the services received are not following the content of the agreement and must be responsible for providing compensation as emphasized in UUPK article 19 and based on contractual liability